Dampak Pengumuman Right Issue terhadap Shareholder Wealth di Bursa Efek Jakarta - Masruroh Masruroh (Bina Nusantara University, 2006)
Article clarifies the impact of right issue announcement on abnormal return that will influence the prosperity of share holder. A research about right issue is an event study research. By event study method can be known is there an impact of abnormal stock price because unanticipated event. Stock price is assumed can reflected the real value of a company, that is a reflection of all future cash flow that discount and include all relevant information.